Preinoculation of Soybean Seeds Treated with Agrichemicals up to 30 Days before Sowing: Technological Innovation for Large-Scale Agriculture - Ricardo Silva Araujo; Sonia Purin da Cruz; Edson Luiz Souchie; Thomas Newton Martin; André Shigueyoshi Nakatani; Marco Antonio Nogueira; Mariangela Hungria (International Journal of Microbiology)
The cultivation of soybean in Brazil experienced an expressive growth in the last decades. Soybean is highly demanding on nitrogen (N) that must come from fertilizers or from biological fixation. The N supply to the soybean crop in Brazil relies on the inoculation with elite strains of Bradyrhizobium japonicum, B. elkanii, and B. diazoefficiens, which are able to fulfill the crop’s N requirements and enrich the soil for the following crop. The effectiveness of the association between N2-fixing bacteria and soybean plants depends on the efficacy of the inoculation process. Seed treatment with pesticides, especially fungicides or micronutrients, may rapidly kill the inoculated bacteria, affecting the establishment and outcome of the symbiosis. The development of technologies that allow inoculation to become a successful component of industrial seed treatment represents a valuable tool for the seed industry, as well as for the soybean crop worldwide. In this article, we report the results of new technologies, developed by the company Total Biotecnologia Indústria e Comércio S/A of Brazil, for preinoculation of soybean seeds with bradyrhizobia, in the presence of agrichemicals. Our results demonstrate improved bacterial survival for up to 30 days after inoculation, without compromising nodulation, N2-fixation, and yield in the field.